Effects of mass transfer parameters on stability and temperature accuracy of Lee model-based numerical scheme: Using vapor chamber as example - Yusuf Rahmatullah; Tsrong-Yi Wen (Case Studies in Thermal Engineering)
Lee model is a numerical scheme capable of simulating full-scale phase change behaviors without a preexisting interface. Lee model incorporates three crucial mass transfer parameters for numerical stability and temperature accuracy, including time relaxation, accommodation coefficient, and interfacial thickness. While the empirical parameter (time relaxation) was emphasized the most in the past, this paper directly links the effects of the experimental conditions (accommodation coefficient) and numerical settings (interfacial thickness) on the stability and temperature accuracy. Using vapor chamber as example, the results indicate that increasing the accommodation coefficient potentially leads to divergence, yet reduces the temperature deviations between interface temperature and saturation temperature. An accommodation coefficient higher than 0.03 does not significantly affect temperature but does compromise numerical stability. In contrast, increasing interfacial thickness does not jeopardize temperature accuracy but increases heat imbalance and makes the solution less conservative. With an accommodation coefficient of 0.03 and a single-layer interfacial thickness of 0.01 mm, the temperature deviations can be well-controlled under 2.4 °C (4.1 %) for the center of evaporator surface and 0.4 °C (0.8 %) for the center of condenser surface.